Da'wah as a Commodity: Analysis of Commodification and Mediatization of Religion in the Religious Talk Show Program of Wisata Hati and Islam Itu Indah - Hikmatussahri Ramadan; Ikbal Nursamsi; Asep Iwan Setiawan (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
In this modern era, da'wah is often exploited for material gain. Da'wah activities should be used to disseminate Islamic values ​​to its adherents, as the saying "Ballighu 'aani Walau ayat" (convey even one verse). This is different from the religious command, this study aims to analyze the phenomenon of commodification and mediatization of religion in the television da'wah programs Wisata Hati and Islam Itu Indah (Islam Itu Indah). Using qualitative methods through literature study and digital observation, this study utilizes Vincent Mosco's Commodification theory and Stig Hjarvard and Stewart Hoover's Mediatization of Religion theory to understand the dynamics of da'wah message production in the media. The results of the study indicate that both programs underwent a commodification process that included the commodification of content, the commodification of audiences, and the commodification of preaching figures, where spiritual values ​​were processed according to market and broadcasting industry demands. Furthermore, mediatization was seen through message visualization, content segmentation, personalization of ustadz figures, and the integration of entertainment elements that formed a new, more emotive and popular religiosity. The important findings of this study formulated the concept of Hybrid Da'wah, namely a da'wah model born from the negotiation between the sacredness of teachings and the rationality of the media industry. This concept shows the paradox between expanding access to da'wah and the potential for simplifying spiritual meaning. This research contributes to the study of religious communication in the context of modern media culture in Indonesia.